Management Information System Database Structure Design Based on the Uncertain Data Objects - Yan Hao; Diao Xing-chun (2008 International Conference on Information Management, Innovation Management and Industrial Engineering, 2008)
The uncertain data objects in the MIS database structure design is a complicated issue and it's worth of discussing. In this paper, we observe the current existing solutions for the uncertain data objects and propose a new method that converts dynamic attributes modifications of the uncertain data objects to the records changing in a fixed-structure table. It effectively implements MIS database structure design based on the uncertain data objects.